Wilckodontics: The State-of-the-Art Combination of Periodontics and Orthodontics – A Narrative Review - Dharmadhikari, Suyog; Shetty, Arvind; Gundavda, Juhi; Bindra, Meher; Choksi, Vrushti; Khan, Simran; Maity, Souranil (Journal of Neonatal Surgery, 2025)
Wilckodontics, or Periodontally Accelerated Osteogenic Orthodontics (PAOO), integrates periodontal and orthodontic techniques to achieve rapid tooth movement through selective alveolar decortication, bone grafting, and orthodontic forces. This method accelerates treatment timelines by leveraging the regional acceleratory phenomenon to enhance alveolar bone remodeling. The procedure employs corticotomy to reduce bone density temporarily, facilitating tooth displacement and enhancing post-treatment stability. Bone grafts promote osteogenesis, ensuring denser alveolar architecture and reducing relapse risk. Introduced in the late 19th century and refined by Henrich Köle and the Wilcko brothers, Wilckodontics has evolved with advancements like laser-assisted corticotomy, micro-osteoperforation, and vibration therapy. These innovations enhance efficiency, reduce invasiveness, and improve patient outcomes. Despite higher costs and surgical demands, Wilckodontics minimizes treatment duration, appliance-associated discomfort, and root resorption while supporting periodontal health. The present narrative review describes this paradigm shift in orthodontics, offering a patient-centered, efficient, and stable alternative to conventional techniques